Shaping a model of transformation in a huge centre of zinc and lead smelting: case study of Szopienice district in the city of Katowice (Poland) - Krzysztofik, Robert; Boroń, Piotr; Dragan, Weronika; Grudniewski, Jakub (Bulletin of Geography. Socio-economic Series, 2024)
The problem of dynamic transformations within complex settlement systems poses an important challenge to planning. This is particularly true of post-industrial and post-mining regions, whose economic past adds an additional dimension affecting development and spatial policy. However, the article highlights the case of a settlement (Szopienice – a district of the city of Katowice in southern Poland) with a heterogeneous genesis in relation to the (post-)mining region in which it is located. Taking into account its economic development founded on zinc and lead metallurgy, the difficulties of development projection are pointed out. These difficulties are emphasised by a focus on the importance of paying attention to this type of locality from several research perspectives. In addition to the aforementioned heterogeneity, the role of “in-between” town locations and spatial peripheralisation is highlighted.